A Brief Provider Training Video Improves Comfort With Recommending the Human Papillomavirus Vaccine. (January 2019) - Kumar, Maya M.; Boies, Eyla G.; Sawyer, Mark H.; Kennedy, Meredith; Williams, Christine; Rhee, Kyung E.
The American Academy of Pediatrics California Chapter 3 created a 20-minute training video targeting barriers to strong provider recommendation of the human papillomavirus (HPV) vaccine. The video included clinical vignettes featuring pediatricians modeling counseling techniques with vaccine-hesitant families. Ninety-six multidisciplinary providers (including pediatric residents) at 6 sites viewed the video and completed baseline and posttest questionnaires assessing their vaccine knowledge, attitudes toward vaccination, and comfort with skills needed to facilitate vaccination. Following the intervention, providers had substantial and statistically significant ( P < .05) improvements in multiple areas assessed, particularly knowledge of the burden of HPV-related disease in males and changes in vaccine response with age; likelihood of "strongly agreeing" that vaccination should not be delayed beyond preadolescence and that HPV vaccine is safe; and feeling "very comfortable" counseling vaccine-hesitant parents and facilitating vaccine completion. This cost-effective and easily disseminated training modality shows promise in increasing provider comfort with HPV vaccine counseling.